(untitled) - Winch, Christopher (London, 1996)
This book includes: Competing conceptions of education, the nature of educational aims, cirricular diversity, arguments about standards and the usefulness of 'value added' measures, the rote of the market, education and quality, inspection and the influence of private sector conceptions of quality on education. This book aims to combine philosophical rigour with practical relevance
Keywords: Education,Giáo dục